Electrodeposition of manganese dioxide coatings onto graphene foam substrates for electrochemical capacitors. (1st July 2023) - Braga, Filipe; Casano, Gabriel; Daniels, Luke M.; Caffio, Marco; Hardwick, Laurence J.
Abstract: Optimisation of electrodeposition routes of birnessite manganese dioxide (MnO2 ) coatings onto 3D graphene foam substrates enabled greater attainable capacitances. Current pulse deposition method resulted in highest achievable areal capacitance of 530 mF/cm 2 under a 10 mA/cm 2 current rate, cycling performance with 91% retention after 9000 cycles, as well as improved rate capability when compared to the cyclic voltammetry or galvanostatic deposition. Introduction of oxygen functional groups to the graphene foam added initial pseudocapacitance and accelerated the rate for nucleation and growth of the MnO2 crystal grains, resulting in an areal capacitance of 410 mF/cm 2 under a 10 mA/cm 2 current rate. However, in this case the increase in specific capacitance was accompanied by sluggish kinetics for charge storage seen via impedance spectroscopy. The charge storage mechanism of the deposited MnO2 films was investigated using in situ Raman microscopy and analysis of peak shifts revealed expansion and contraction of birnessite MnO2, relating to exchange of Na + and H2 O at the MnO2 interface.